2019
DOI: 10.1021/acs.organomet.9b00692
|View full text |Cite
|
Sign up to set email alerts
|

β-Amino Phosphine Mn Catalysts for 1,4-Transfer Hydrogenation of Chalcones and Allylic Alcohol Isomerization

Abstract: Mn complexes with amino acid derived PN ligands were used in the catalytic transfer hydrogenation (TH) of ketone and chalcone substrates in 2-propanol with mild heating. Moreover, chalcones are reduced selectively to the saturated ketone at short times and can be fully converted to the alcohol when reactions are prolonged. The mechanism of chalcone reduction was briefly considered. Allylic alcohols are not reactive in 2-propanol, but quantitative isomerization occurs in toluene. Thus, we suspect that the allyl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Most of these systems relies on bidentate tricarbonyl Mn-NN complexes and are selective for C=O bond reduction. However, TH of chalcones catalyzed by PN complex developed by Lacy [23] proceeds selectively at the conjugated C=C bond, being consistent with the results of hydrogenation of these substrates using related Mn-PN complex [24]. Although demonstrating reasonable activities, there was still a gap to be bridged to approach the activity recorded with catalytic systems involving noble metals.…”
Section: Reduction Of Ketones Aldehydes Imines Nitroarenes and N-heterocyclessupporting
confidence: 75%
“…Most of these systems relies on bidentate tricarbonyl Mn-NN complexes and are selective for C=O bond reduction. However, TH of chalcones catalyzed by PN complex developed by Lacy [23] proceeds selectively at the conjugated C=C bond, being consistent with the results of hydrogenation of these substrates using related Mn-PN complex [24]. Although demonstrating reasonable activities, there was still a gap to be bridged to approach the activity recorded with catalytic systems involving noble metals.…”
Section: Reduction Of Ketones Aldehydes Imines Nitroarenes and N-heterocyclessupporting
confidence: 75%
“…A formal change of pyridine moiety in picolylamine system by phosphine was reported by the group of Lacy in 2019 (Scheme 55) [88]. It was shown that complexes 124 bearing PN ligands easily available from optically pure amino-acids were competent catalyst for transfer hydrogenation of various ketones typically at 60 °C using 0.5 mol% catalyst loading albeit with negligibly low enantiomeric induction (11% ee max).…”
Section: Scheme 52mentioning
confidence: 93%
“…Later, Lacy reported that bidentate aminophosphine Mn( i ) complex Mn59 showed a comparable TON for the TH of ketones under similar reaction conditions (Table 8, entry 10). 164 The catalyst showed exceptional behavior towards α,β-unsaturated ketones. The reduction was thought to proceed via 1,4-hydride addition followed by isomerization, resulting in saturated ketones.…”
Section: Manganese-catalyzed Hydrogenation Reactionsmentioning
confidence: 98%